Mapping poverty rates in Chile with night lights and fractional multinomial models. Issue 4 (21st April 2021) - Cecchini, Simone; Savio, Giovanni; Tromben, Varinia
Abstract: This paper analyzes the relation between night lights and poverty rates in Chile using information derived from the US Earth Observations Group through the Visible Infrared Imaging Radiometer Suite (VIIRS), Day/Night Band. Official poverty data are modeled at the municipality level with a fractional multinomial logit model. Indicators of night lights are applied to the estimated model to predict poverty and extreme‐poverty rates of municipalities for which official data are not available, and estimates are aggregated at provincial, regional, and national levels using population data. Results are consistent with official estimates published for the year 2015 and can be effectively used for policy purposes to derive maps of poverty indices with a definition of 500 m 2 . Abstract: 本論文は、可視赤外撮像機放射計(Visible Infrared Imaging Radiometer Suite:VIIRS)、24時間対応バンドにより米国地球観測グループから得られた情報を用いて、チリにおける夜間光と貧困率の間の関連性を分析する。公式の貧困データは、分数多項ロジットモデルを用いて自治体レベルでモデル化した。公式データが入手できない自治体の貧困率と極度貧困率を予測するために、夜間光の指標を推定モデルに適用し、人口データを用いて、州、地域、国レベルで推定値を集計した。結果は、2015年に公表された公式推計値と一致しており、政策のために500 m 2 の解像度で貧困指数の地図を作成するのに効果的に使用することができる。 Abstract: Este artículo analiza la relación entre el alumbrado nocturno y los índices de pobreza en Chile por medio de información obtenida del Grupo de Observaciones de la Tierra de los Estados Unidos a través de imágenes de la banda Dia/Noche del VIIRS ( Visible Infrared Imaging Radiometer Suite ). Se usaron los datos oficiales de pobreza a nivel de municipio en un modelo logit multinomial fraccional. Los indicadores de luces nocturnas se aplicaron al modelo estimado para predecir las tasas de pobreza y de extrema pobreza de los municipios para los que no se dispone de datos oficiales, y las estimaciones se agregaron a nivel provincial, regional y nacional utilizando datos de la población. Los resultados están en consonancia con las estimaciones oficiales publicadas para el año 2015 y pueden utilizarse eficazmente a efectos de políticas para obtener mapas de índices de pobreza con una definición de 500 m 2 .